Risiko Bisnis, Profitabilitas, dan Struktur Aktiva Sebagai Penentu Struktur Modal Perusahaan Makanan dan Minuman - Meitriyani, Ni Wayan; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 31 No 11 (2021), 2021)
The purpose of this study was to determine the effect of business risk, profitability, and asset structure on capital structure. This study takes samples from manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sample used is purposive sampling. The analysis technique used is multiple linear regression. The results of business risk research have a significant positive effect on the capital structure of Food and Beverage Companies Listed on the IDX in 2015-2019 while profitability has a significant negative effect on the capital structure of Food and Beverage Companies Listed on the IDX, and asset structure has a significant positive effect on the capital structure in Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2015-2019. Keywords : Food and Beverage; Business Risk; Profitability; Asset Structure.